2022
DOI: 10.3389/fgene.2022.994471
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic regulation of growth, reproduction, disease resistance and stress responses in aquaculture

Abstract: Major progress has been made with genomic and genetic studies in aquaculture in the last decade. However, research on epigenetic regulation of aquaculture traits is still at an early stage. It is apparent that most, if not all, aquaculture traits are regulated at both genetic and epigenetic levels. This paper reviews recent progress in understanding of genetic and epigenetic regulation of important aquaculture traits such as growth, reproduction, disease resistance, and stress responses. Although it is challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 258 publications
0
17
0
Order By: Relevance
“…When CGI undergo methylation modification, the methylation level of promoter region changes and generally accompanied by the inhibition of gene transcription, resulting in gene silencing ( 26 , 27 ). The distribution of upstream and downstream methylation levels of genes indicated high methylation levels in this genomic region, which is common in mammalian, especially in aquatic animals, and negatively regulated the level of gene expression ( 28 , 29 ). These results indicated that the spontaneous DNA methylation pattern in turbot was similar to other species, indicating that the DNA methylation patterns among vertebrates are relatively conserved to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When CGI undergo methylation modification, the methylation level of promoter region changes and generally accompanied by the inhibition of gene transcription, resulting in gene silencing ( 26 , 27 ). The distribution of upstream and downstream methylation levels of genes indicated high methylation levels in this genomic region, which is common in mammalian, especially in aquatic animals, and negatively regulated the level of gene expression ( 28 , 29 ). These results indicated that the spontaneous DNA methylation pattern in turbot was similar to other species, indicating that the DNA methylation patterns among vertebrates are relatively conserved to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…It was found from the WGBS results that many DMGs were significantly enriched in multiple immune-related pathways, such as MAPK signaling pathway, Wnt signaling pathway. Among them, MAPK signaling pathway plays a key role in apoptosis and the interaction between bacteria and host in cancer and immune system ( 29 , 30 ). At the same time, a large number of immune-related DEGs were screened and analyzed from the transcriptome sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that our study was focused on genetic markers detected by their association with divergent selection (naïve vs. affected stocks; non‐infected vs. infected individuals), but we cannot discard other models of selection operating in our scenario, such as overdominance, which has demonstrated to be involved in tolerance or resistance to stress or pathologies in other studies (Di et al, 2015; Gallaga‐Maldonado et al, 2020; Maynard et al, 2016). Also, the putative role of epigenetic changes and their transmission across generations (“priming”; Eirin‐Lopez & Putnam, 2019; Fallet et al, 2022; Johnson et al, 2020; Liu et al, 2022; Potts et al, 2021) should be evaluated to understand the quick resilience acquisition against marteiliosis observed in common cockle. In this regard, we have compiled a valuable biological material, both from different wild stocks as well as from families of both stocks obtained at hatchery, to investigate the putative epigenomic “priming” underlying marteiliosis resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst such studies identified CREs at particular loci, epigenetic sequencing methods can capture chromatin accessibility and TF-binding at the genome-wide level 13 . Only a handful of studies, all using DNA methylation, have applied epigenetic approaches to study adaptive traits in tilapia 14 ; this includes the regulation of tilapia growth 15-17 , sexual dimorphism 18 , and sex determination 19,20 . ChiP-seq approaches have also been used to map active promoter elements associated with Nile tilapia fin development 21 .…”
Section: Introductionmentioning
confidence: 99%